Palbociclib plus endocrine therapy significantly enhances overall survival of HR+/HER2− metastatic breast cancer patients compared to endocrine therapy alone in the second‐line setting: A large institutional study. Issue 12 (3rd March 2022) - Ha, Min Jin; Singareeka Raghavendra, Akshara; Kettner, Nicole M.; Qiao, Wei; Damodaran, Senthil; Layman, Rachel M.; Hunt, Kelly K.; Shen, Yu; Tripathy, Debu; Keyomarsi, Khandan
Abstract: Cyclin‐dependent‐kinase‐4/6 inhibitor (CDK4/6i) plus endocrine therapy (ET) is standard of care for patients with advanced hormone receptor (HR)‐positive, HER2‐negative breast cancer (BC). The Breast Medical Oncology database at MD Anderson Cancer Center (MDACC) was analyzed to assess effectiveness of the CDK4/6i palbociclib plus ET compared to ET alone. From a total of 5402 advanced HR+ HER2− BC patients referred to MDACC between 1997 and 2020, we identified eligible patients who received palbociclib in combination with first‐line (n = 778) and second‐line (n = 410) ET. We further identified "control" patients who received ET alone in the first‐line (n = 2452) and second‐line (n = 1183) settings. Propensity score matching analysis was conducted to balance baseline demographic and clinical characteristics between palbociclib and control cohorts to assess the effect of palbociclib treatment on progression‐free survival (PFS) and overall survival (OS). For propensity‐matched‐cohort in the first‐line setting (n = 708), palbociclib group had significantly longer median PFS (17.4 vs 11.1 months; P  < .0001) compared to controls. Median OS (44.3 vs 40.2 months) did not show a statistically significant benefit in the first line setting. However, in the second‐line setting, with 380 propensity‐matched‐cohort, the palbociclib group had significantly longer PFS (10 vs 5 months, P  < .0001) as well as OS (33 vs 24 months; P  < .022), compared to controls. We conclude that in this single center analysis of a large cohort of metastatic HR+ HER2− BC patients, palbociclib in combination with ET was associated with improved PFS in both first‐line and second‐line settings and OS in the second‐line setting compared to ET alone cohort. Abstract : What's new? Real‐world data may give a more representative picture of the effectiveness and tolerability of treatment in the general population compared to clinical trials. Using a large, highly‐curated database of metastatic HR‐positive and HER2‐negative breast cancer patients, the authors present real‐world outcomes of treatment with palbociclib and endocrine therapy (ET) in the first‐line and second‐line settings, without confounding effects of prior chemotherapy. Rigorous propensity score matching reveals that palbociclib combined with ET was associated with both improved progression‐free survival in the first‐line and second‐line settings and overall survival in the second‐line setting compared to ET alone.